ANALYSIS OF STUDENTS’ MATHEMATICAL ABSTRACTION ABILITY BY USING DISCURSIVE APPROACH INTEGRATED PEER INSTRUCTION OF STRUCTURE ALGEBRA II - Elsa Komala (IKIP Siliwangi and I-MES, 2018)
This research is subject to describe students' mathematical abstraction ability using the discursive approach of peer instruction integration, to get an idea about the problems faced by students and to study about the interventions needed by students to overcome the problems. This research using the quantitative descriptive approach with pre-experimental design: the one-shot case study design, which is done to the students in the course of the structure of algebra II. Based on the data analysis, result of the research shows that ability of students' mathematical abstraction using the discursive approach of peer instruction integration in the course of the structure of algebra II does not exceed 85% of ideal criteria determined. Obstacles faced by students such as cognitive obstacles, genetic and psychological obstacles, didactic obstacles, epistemological obstacles. Interventions that need to be given such as by providing reinforcement to the mastery of prerequisite material, conditioning through drill, practice, and exercise, providing scaffolding, raises students awareness of what they learn, convergent interventions in the form of a closed-ended investigative question.